2022
DOI: 10.1177/03635465211073339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mechanical Stimulation Combined With Platelet-Rich Plasma on Healing of the Rotator Cuff in a Murine Model

Abstract: Background: Mechanical stimulation and platelet-rich plasma (PRP) have been shown to be beneficial for healing of the bone-tendon interface (BTI), but few studies have explored the efficacy of a combination of these applications. We investigated the effect of mechanical stimulation combined with PRP on rotator cuff repair in mice. Hypothesis: Mechanical stimulation combined with PRP can enhance BTI healing in a murine model of rotator cuff repair. Study Design: Controlled laboratory study. Methods: A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…As a complicated mixture of these growth factors, PRP effectively stimulates MSC proliferation, synthesizing the extracellular matrix proteins (proteoglycans, collagen, etc), and promoting angiogenesis. 24,32,38,43 Our in vitro study confirmed that the MSCs cocultured in APG proliferated significantly better than the cell culture plate. In addition, under osteogenic or chondrogenic induction, the MenSCs cocultured in APG expressed significantly higher osteogenic-specific mRNA (Runx2) or chondrogenic-specific mRNA (Sox9) than the BMSCs or the MenSCs cultured without APG.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As a complicated mixture of these growth factors, PRP effectively stimulates MSC proliferation, synthesizing the extracellular matrix proteins (proteoglycans, collagen, etc), and promoting angiogenesis. 24,32,38,43 Our in vitro study confirmed that the MSCs cocultured in APG proliferated significantly better than the cell culture plate. In addition, under osteogenic or chondrogenic induction, the MenSCs cocultured in APG expressed significantly higher osteogenic-specific mRNA (Runx2) or chondrogenic-specific mRNA (Sox9) than the BMSCs or the MenSCs cultured without APG.…”
Section: Discussionsupporting
confidence: 66%
“…APG is a gel material of PRP that is capable of releasing growth factors such as transforming growth factor–β, platelet-derived growth factor, insulin-like growth factor, basic fibroblast growth factor, and vascular endothelial growth factor. 24,32,38,43 The transplanted MenSCs@APG may be activated by these released growth factors and then proliferated quickly, as well as spatially differentiated into the osteogenic or chondrogenic lineage, thus facilitating RC healing. Indeed, our in vitro study determined that the MenSCs cultured within APG showed better osteogenic or chondrogenic differentiation than BMSCs alone.…”
Section: Discussionmentioning
confidence: 99%
“…After preparation for the surgery, the skin flap of the right hind limb of the mice was lifted, with later cutting at the tendon of the right hind limb of the mice to simulate the damage to the tendon of the acute lower limb due to motor injury. 15 Poly(lactide-co-glycolide) acid fibers and PLGA-PDGF-AA fibers were fixed using an interrupted suture technique and 8/0 silk was thread at the Achilles tendon of the right hind limb of tendon injured mice. Our method of fixation was to wrap the tendon after tendon injury and then fix it with 8/0 silk.…”
Section: In Vivo Examination Of Pdgf-aa-modified Plga Fibersmentioning
confidence: 99%
“…These autologous blood biologics products contain a high concentration of platelets, which release growth factors and cytokines 8 that promote tissue healing by inducing cell differentiation, extracellular matrix production, and angiogenesis 9,10 . Several studies have demonstrated their effectiveness and safety 11,12 . Based on their properties, platelet‐rich products can be classified as platelet‐rich plasma (PRP) and platelet‐rich fibrin (PRF).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Several studies have demonstrated their effectiveness and safety. 11,12 Based on their properties, platelet-rich products can be classified as platelet-rich plasma (PRP) and platelet-rich fibrin (PRF). PRP and PRF are extracted from the blood by centrifugation but prepared differently.…”
Section: Introductionmentioning
confidence: 99%